2021
DOI: 10.21203/rs.3.rs-156120/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Aerobic Training Progression on Blood Pressure in Individuals With Hypertension: A Systematic Review With Meta-Analysis and Meta-Regression

Abstract: Objective: To analyze, through a systematic review with meta-analysis, the effects of aerobic training with and without progression on systolic blood pressure (SBP) and diastolic blood pressure (DBP) in hypertensive adults.Method: The search for the studies was carried out in the PubMed, Cochrane Central, SPORTDiscus and LILACS databases. Clinical trials that analyzed the effect of aerobic training, lasting at least six weeks, on blood pressure in hypertensive individuals comparing with a control group without… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…This may indicate the synergistic mechanism of renin-angiotensin-aldosterone inhibitor based anti-hypertensive drugs and exercise [89]. Whilst many trials based on hypertensive patients have shown that aerobic exercise reduced BP [82,90], most have not attempted to peel this back and assess effects of medication, aerobic exercise or a combination of both.…”
Section: Synergy Between Exercise and Pharmacotherapymentioning
confidence: 99%
“…This may indicate the synergistic mechanism of renin-angiotensin-aldosterone inhibitor based anti-hypertensive drugs and exercise [89]. Whilst many trials based on hypertensive patients have shown that aerobic exercise reduced BP [82,90], most have not attempted to peel this back and assess effects of medication, aerobic exercise or a combination of both.…”
Section: Synergy Between Exercise and Pharmacotherapymentioning
confidence: 99%